Chocolate nations : living and dying for cocoa in West Africa - Ryan, Orla (African arguments., 2011)
From the thousands of children who work on plantations to the smallholders who harvest the beans, Chocolate Nations reveals the hard economic realities of our favourite sweet. This vivid and gripping exploration of the reasons behind farmer poverty includes the human stories of the producers and traders at the heart of the West African industry. Provocative and eye-opening, Chocolate Nations exposes the true story of how the treat we love makes it onto our supermarket shelves.